ANALISIS PEMASARAN DAN TRANSMISI HARGA PADA PETANI KARET POLA SWADAYA DI DESA GOBAH KECAMATAN TAMBANG KABUPATEN KAMPAR - Riat Shuhada; Ermi Tety; Suardi Tarumun (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The purpose of this research is to know and analyse : 1) Channel, margin, marketing eficiency and farmer income; 2) Correlation between bokar payment from factory with price to farmer 3) Price influence (price transmission elasticity) bokar at factory level and price at farmer level 4) Market structure. This research using survey method. Doing sampling by purposive sampling on 20 rubber farmer with life plant around 15-25 years old. Doing sampling on seller and factory by using snowball sampling method with follow it’s marketing channel. The result at Gobah Village Tambang District kampar Regency there is on marketing channel (homogen). Farmer to the seller and the seller to factory. The lowest price at farmer level Rp.5.550 /kg, the highest price at farmer level Rp. 9.400/kg, the lowest price at factory level Rp. 7.025/kg, the highest price at factory level Rp. 10.925/kg. Farmer income marketing margin which price payed by factory to the seller since Febuari 2014-Januari 2015 around Rp.1,58,33 and farmer income around 75.25% marketing efficiency around 16.88%. Correlation value at farmer level and price at factory level 0,924%. Price transmission elasticity at farmer level and at factory level around 0.850%. Market structure are dominan market with kr 68,1%. Keywords : Marketing, Margin, Price Transmision, Elasticity and market structure